Crossing the border; Historical and linguistic divides among the Bunaq in central Timor - Schapper, Antoinette (Wacana, Journal of the Humanities of Indonesia, 2011)
The Bunaq are a Papuan language-speaking people straddling the border of Indonesian West Timor and independent East Timor. This paper looks at the history of the Bunaq as a "border" people in Timor. "Border" is interpreted here in two ways, as referring to: (i) a political division, the boundary line separating one country from another, and (ii) a linguistic division, the distinguishing line between Papuan and Austronesian languages. I examine the effect that the Bunaq position at the political and linguistic borders of Timor has had on the people and their language.